Pengaruh, Hutang Jangka Pendek dan Penjualan Terhadap Pertumbuhan Laba Perusahaan - Eka, Anisa; Marpaung, Bintang Sahala (Jurnal Ilmiah Manajemen Kesatuan, 2017)
Income is one important indicator to assess performance of a company. As the most liquid assets of the company, cash is important to measure the adequacy of the company's costs needed to repay debts and finance its activities. The purpose of this study was to determine the effect of cash on earnings, the influence of short-term debt on earnings growth, the influence of sales on profit growth, and how cash, short-term debt and the sales are affecting the profit growth in the company PT. Indocement Tunggal Prakasa. Tbk, PT. Mayora Indah. Tbk, and PT. Astra Otoparts. Tbk. The year of observation is of period 2005-2014, and types of data used are secondary data derived from the company's official website as well as the Indonesian Stock Exchange. The analytical method used in this study is regression analysis to find variables that have effects either partially or simultaneously. Based on the results of research conducted over a period of 10 years from 2005 to 2014, it can be concluded that the Treasury had no significant effect on earnings growth partially in PT Indocement single prakasa, PT Mayora Indah Tbk and PT Astra, short-term debt partially had not significant effect on profit growth PT Indocement PT Mayora and PT Astra. Sales had not partially significant effect on earnings growth at PT Indocemet Tunggal Tbk prakasa whereas in PT Mayora Indah Tbk and PT Astra Otoparts it had significantly affected on earnings growth.